Use of electrospinning to develop antimicrobial biodegradable multilayer systems: encapsulation of cinnamaldehyde and their physicochemical characterization - Cerqueira, Miguel A. (2016)
In this work, three active bio-based multilayer structures, using a polyhydroxybutyrate-co-valerate film with a valerate content of 8 % (PHBV8) as support, were developed. To this end, a zein interlayer with or without cinnamaldehyde (CNMA) was directly electrospun onto one side of the PHBV8 film and the following systems were developed: (1) without an outer layer; (2) using a PHBV8 film as outer layer; and (3) using an alginate-based film as outer layer. These multilayer structures were characterized in terms of water vapour and oxygen permeabilities, transparency, intermolecular arrangement and thermal properties. The antimicrobial activity of the active bio-based multilayer systems and the release of CNMA in a food simulant were also evaluated. Results showed that the presence of different outer layers reduced the transport properties and transparency of the multilayer films. The active bio-based multilayer systems showed antibacterial activity against Listeria monocytogenes being the multilayer structure prepared with CNMA and PHBV outer layers (PHBV + zein/CNMA + PHBV) the one that showed the greater antibacterial activity. The release of CNMA depended on the multilayer structures, where both Fick's and Case II transport-polymer relaxation explained the release of CNMA from the multilayer systems.